A primary splenic epithelial cyst: rare case report - Chandak, Unmed; Mitra, Arti; Kamble, Archana (International Surgery Journal, 2018)
Splenic cysts are rare, most of them being hydatid cysts. Our case is about a primary (true) splenic epithelial cyst. A 21-year-old female patient presented to casualty with pain in the upper left abdomen. On being investigated with by sonography she was found to have a solitary cystic lesion in the spleen. Her contrast enhanced computed tomography of the abdomen and pelvis revealed a 10.9 × 11.4 × 12.0 cm cystic lesion of the spleen, probably a hydatid or primary splenic epithelial cyst. Due to the large size of the cyst, an open surgical approach was planned. On exploratory laparotomy via a left subcostal incision, a solitary cyst involving >75% of the splenic parenchyma was discovered. Total splenectomy was done as splenic parenchyma could not be functionally salvaged. Histopathological investigation showed a primary epithelial splenic cyst. The patient recovered uneventfully.